A Combined Experimental and Theoretical Study of the Versatile Reactivity of an Oxocerium(IV) Complex: Concerted Versus Reductive Addition. Issue 46 (26th July 2019) - Castro, Ludovic; So, Yat‐Ming; Cho, Chang‐woo; Lortz, Rolf; Wong, Kai‐Hong; Wang, Kai; Arnold, Polly L.; Au‐Yeung, Ka‐Chun; Sung, Herman H.‐Y.; Williams, Ian D.; Leung, Wa‐Hung; Maron, Laurent
Abstract: A combined experimental and theoretical investigation on the cerium(IV) oxo complex [(LOEt )2 Ce(=O)(H2 O)]⋅ MeC(O)NH2 (1 ; LOEt − =[Co(η 5 ‐C5 H5 ){P(O)(OEt)2 }3 ] − ) demonstrates that the intermediate spin‐state nature of the ground state of the cerium complex is responsible for the versatility of its reactivity towards small molecules such as CO, CO2, SO2, and NO. CASSCF calculations together with magnetic susceptibility measurements indicate that the ground state of the cerium complex is of multiconfigurational character and comprised of 74 % of Ce IV and 26 % of Ce III . The latter is found to be responsible for its reductive addition behavior towards CO, SO2, and NO. This is the first report to date on the influence of the multiconfigurational ground state on the reactivity of a metal–oxo complex. Abstract : Reaction mechanisms : Evidence of intermediate spin‐state behavior in reactivity for the cerium‐oxo complex are given by a combined experimental/theoretical study (see scheme).